Pengaruh Kepercayaan Diri dan Kemampuan Komunikasi Matematika Terhadap Hasil Belajar Matematika Siswa - Putu Sri Indah Yulia Dewi; Nani Kurniati; Wahidaturrahmi Wahidaturrahmi (Griya Journal of Mathematics Education and Application, 2021)
This research aims to find out the influence of self-confidence on students’ mathematics learning outcome, the influence of mathematics communication ability on students’ mathematics learning effect, and the influence of self-confidence and mathematics communication ability on students’ mathematics learning outcome of 8th grade SMPN 22 Mataram academic year 2019/2020. This type of research was ex post facto. The sample of this research were 44 students with total sampling technique. Data collection techniques in this reseacrh using questionnaire, test and documentation. The instrument of this research was in the form of a confidence questionnaire, a test of mathematics communication ability, and documentation of students’ mathematics learning outcome of 8th grade SMPN 22 Mataram. From the data analysis obtained, there was no influence of self-confidence on students’ mathematics learning effect of 8th grade SMPN 22 Mataram. Whereas for mathematics communication ability there was found an influence on students’ mathematics learning effect of 8th grade SMPN 22 Mataram with the coefficient of determination of 83.7%. The results of data analysis also showed that there was a significant influence between students' self-confidence and mathematics communication ability on students’ mathematics learning effect of 8th grade SMP 22 Mataram with the coefficient of determination of 83.1%.